The impact of pain spread on the outcome of multidisciplinary therapy in patients with chronic musculoskeletal pain: a prospective clinical study in 389 patients - Moradi, Babak; Zahlten-Hinguranage, Anita; Barié, Alexander; Caldeira, Fernanda; Forró, Philipp Arne Florian; Schiltenwolf, Marcus; Neubauer, Eva (European journal of pain, 2010)
Background: Musculoskeletal pain represents a continuous process ranging from single-site to multiple-site pain, with an increase in pain sites accompanied by an increasing risk of chronification and the development of further comorbidities. Within this context, the impact of pain spread on therapy outcome is still unknown. Aims: This prospective clinical study aimed to evaluate whether and to what extent patients with pain at multiple sites would also benefit from multidisciplinary therapy or whether therapy success is limited by pain spread. Methods: Patients’ characteristics were assessed, including socio-demographic variables, occupational and workplace characteristics, pain intensity and dimensions of pain, psychological aspects and functional back capacity, as well as the generic health status. Data were prospectively collected at day 1 (baseline) and at 6-month follow-up from a sample of 389 patients undergoing multidisciplinary treatment. Patients were distributed into three groups based on the number of pain sites (single-site, dual-site and multiple-site) and the outcome parameters were compared. Results: All three groups improved significantly from baseline to the 6-month follow-up. Compared to patients with multiple-site pain, patients with single-site and dual-site pain displayed significantly better outcome on almost all measures. Only the subcategory mental health of the SF-36 did not show any statistically significant differences among the three groups. Conclusions: Our results display that patients with two or more pain sites also improve significantly in the outcome measures. Therefore, treatment should be offered independent of the extent of pain spread. However, therapy is significantly less successful in patients with pain at multiple sites.